1985
DOI: 10.1037/0033-295x.92.3.317
|View full text |Cite
|
Sign up to set email alerts
|

"To carve nature at its joints": On the existence of discrete classes in personality.

Abstract: In principle, units of personality may be of two varieties: dimensional variables, which involve continuously distributed differences in degree, and class variables, which involve discretely distributed differences in kind. There exists, however, a prevailing and rarely questioned assumption that the units of personality are continuous dimensions and an accompanying prejudice against class variables. We examine this prejudice, the arguments that generated it, and those that uphold it. We conclude that these ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
539
7
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(563 citation statements)
references
References 112 publications
(140 reference statements)
14
539
7
3
Order By: Relevance
“…First, by locating nature's joints (Gangestad & Snyder 1985) it works against the confl ation of emotions that are in some ways alike, enabling scientifi c advances by unconfounding discrete phenomena. Second, it stimulates study of the undergirding of the category boundaries, such as necessary features or discrete cultural schemata, eliciting conditions or physiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, by locating nature's joints (Gangestad & Snyder 1985) it works against the confl ation of emotions that are in some ways alike, enabling scientifi c advances by unconfounding discrete phenomena. Second, it stimulates study of the undergirding of the category boundaries, such as necessary features or discrete cultural schemata, eliciting conditions or physiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, statistical methods for adjudicating between them are only beginning to see widespread use, largely through the popularization of Meehl and Golden's (1982) taxometric methods. To date there have been several taxometric investigations of psychopathological syndromes ( e.g., Golden & Meehl, 1979;Harris, Rice, & Quinsey, 1994;Haslam & Beck, 1994;Lenzenweger & Korfi ne, 1992;Trull, Widiger, & Guthrie, 1990;Tyrka, Haslam, & Cannon, 1995) and personality variables (Gangestad & Snyder, 1985;Strobe, 1989). Although all of these studies have tested for categories of people, taxometric analysis has also been used in a study of types of social relationship (Haslam, 1994).…”
mentioning
confidence: 99%
“…Research suggests that self-monitoring is a stable aspect of personality through the lifespan (Gangestad & Snyder, 1985;Jenkins, 1993, p. 84). A meta-analytic review of the literature on self-monitoring in the workplace concluded that this scale has sound psychometric properties, as evidenced by high levels of internal consistency, reliability, and predictive validity (Day, Schleicher, Unckless, & Hiller, 2002).…”
Section: Self-monitoringmentioning
confidence: 99%
“…Thurstone und alle, die seiner ‚amerikanischen Schule' folgten, hielten das initiale orthogonale Faktorenmuster, das eine Zentroid-, Hauptachsen-oder Hauptkomponentenanalyse generiert, für "im allgemeinen nicht interpretierbar" (Überla, 1971, 175) (Fittkau, 1968, Butler, 1969 (Andresen, 1998, p. 74 Hamilton, 1960, Lumsden, 1961, Leventhal & Stedman, 1970 Gangestad & Snyder (1985) und Snyder & Gangestad (1985 (Gorsuch, 1974, p. 191 (Burt, 1954, p. 16). Burt nahm routinemäßig zwar auch eine Umwandlung der bipolaren Initialfaktoren zugunsten einer unipolaren Lösung vor, die er ‚Gruppenfaktorlösung' nannte.…”
Section:  Zur Abwertung Initialer Faktorstrukturenunclassified